Clinical features of protracted bacterial bronchitis in children - Chi, Fanfan (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2015)
OBJECTIVE: To analyze the clinical characteristics of protracted bacterial bronchitis (PBB) in children